Sustainable Operation Mode Choices for Second-Hand Inspection Platforms - Han Yue; Min Huang (Systems)
The sale of second-hand goods has formed a complete industrial chain, and second-hand product testing is a crucial part of it. Second-hand inspection platforms (SIPs) have achieved remarkable commercial success by providing inspection services that alleviate consumers’ quality concerns. Different SIPs typically adopt various operation modes, such as consignment, resale, or hybrid modes. Appropriate operation modes not only benefit SIPs in maintaining profitability but also contribute to the sustainable development of the sharing economy. In order to realize the sustainable operation of second-hand inspection platforms, we construct a platform-dominated Stackelberg model to explore the motivations behind SIPs’ choices of different operation modes and investigate the impacts of changes in the inspection service level on the platform’s optimal decisions and market performance. System data analysis results show that the cost of guarantee significantly influences SIPs’ choices of operation modes, specifically; SIPs are inclined to adopt consignment mode or resale mode when the cost of guarantee is relatively high or low, respectively, and choose hybrid mode when the cost of guarantee is moderate. Furthermore, in the presence of inter-channel competition, if the inspection failure loss is relatively high, SIPs may lower the prices of used products as the inspection service level increases. Additionally, although inspection service can disclose the true quality of used products, a higher inspection service level may attract more low-quality sellers into the market when the inspection failure loss is substantial. Finally, under the resale mode, consumer surplus and social welfare will decrease with the inspection service level. Conversely, under the consignment or hybrid mode, both consumer surplus and social welfare will increase with the inspection service level when the inspection failure loss is relatively low.